Thyroid Status in Pregnant &Non Pregnant Women - Tarwey, Avnish Kumar; Yadav, Renu; Singh, Rajat Kumar; Tarwey, Piyush (Journal of Neonatal Surgery, 2025)
Introduction Thyroid function is altered during pregnancy. Various factors plays an important role in the development of thyroid gland during pregnancy. Thyroid hormone during pregnancy also plays an important role for neuroendocrine development of the fetus. Thyroid function is assessed to evaluate thyroid abnormalities, and monitor pre-existing thyroid disease. The interpretation of thyroid status is based on the normal physiological changes during pregnancy, the iodine adequacy, medical consideration, medication and ambient goitrogens in different geographical region.(1-2) . Materials and Methods Study group of 50 pregnant women in each trimester as case group and control group of 50 non pregnant healthy women at RIMS Ranchi. Serum FT3,FT4 and TSH measured by chemiluminescent microparticle immunoassay(CMIA) method. Result Conclusion. In the third trimester, the mean FT4 signiﬁcantly decreased than the mean for non-pregnant women. Mean FT3 values showed declining over the trimesters relative to the non-pregnant control group that were signiﬁcant in second and third trimesters. In each trimester, the mean TSH levels of pregnant women were lower than the mean level of non-pregnant but were not statistically signiﬁcant in second and third trimesters possibly due to increased TBG, increased formation of deiodinase by placenta and increased in Albumin and free fatty acid3